Bamboo: the forgotten versatile materials - Abdullah, Fadzidah; Sanusi, Aliyah Nur Zafirah; Azmin, Aida Kesuma; Yusof, Zeenat Begam (Springer, Cham, 2021)
This This chapter enquires the potentials of bamboo as building materials and evaluates the strategies of using bamboo based on case studies of existing bamboo buildings throughout the tropical regions of Southeast Asia. Bamboo is well known to be a versatile material for the building industry, yet its usage in building construction is very limited that people disregard the potential of bamboo as a versatile material for the sustainable construction industry. Research and observation have shown that bamboo buildings are relevant to the modern era, and the usage of bamboo as building materials could support the call of sustainable development. Hence, bamboo deserves to be re-established in the construction industry, for the construction of both modern and traditional architecture.